Innovation of Local Wisdom Based Pop-Up Book Learning Media to Foster Students’ Character Development - Alphonsus Ulung Tegar Oktovian; Dionisius Heckie Puspoko Jati; Nani Mediatati; Rebeka Sri Minati (Universitas Negeri Semarang, 2026)
Background –The background of this research is based on the perception that learning geometry at the elementary school level is often considered monotonous and less interesting, due to the lack of varied teaching methods and the lack of material connection with students' daily lives. Purpose –To increase students' interest in learning, creativity, and understanding, this research integrates the traditional Mountain Tread gamewith the concept of Fibonacci. Method/Approach–With a qualitative approach, data collection was done through observation, interviews, and documentation during the learning process. Findings –The results showed that the use of this media was able to improve students' understanding of geometric shapes and patterns, while stimulating their creativity in forming and exploring geometric patterns based on the Fibonacci concept. Conclusions–In conclusion, combining traditional games and the Fibonacci concept is an effective strategy in developing creativity and understanding of geometry at the elementary school level, with the advantage of keeping up with the times while preserving local culture. Novelty/Originality/Value - This study offers an innovative integration of local wisdom content with three-dimensional Pop-Up Book design as a character education tool.